Photo-Protection in the Centric Diatom Coscinodiscus granii is Not Controlled by Chloroplast High-Light Avoidance Movement - Goessling, Johannes W.; Cartaxana, Paulo; Kühl, Michael (Frontiers in Marine Science, 2016)
Diatoms are important phototrophs in the worlds’ oceans contributing approximately 40% of the global primary photosynthetic production. This is partially explained by their capacity to exploit environments with variable light conditions, but there is limited knowledge on how diatoms cope with changes in the spectral composition and intensity of light. In this study, the influence of light quality and high irradiance on photosynthesis in the centric diatom Coscinodiscus granii was investigated with microscopic imaging and variable chlorophyll fluorescence techniques. Determination of the wavelength-dependent functional absorption cross-section of photosystem (PS) II revealed that absorption of blue light (BL) and red light (RL) was 2.3-fold and 0.8-fold that of white light (WL), respectively. Hence, BL was more efficiently converted into photo-chemical energy. Excessive energy from BL was dissipated via non-photochemical quenching (NPQ) mechanisms, while RL apparently induced only negligible NPQ even at high irradiance. A dose dependent increase of cells exhibiting an altered chloroplast distribution was observed after exposure to high levels of BL and WL, but not RL. However, no effective quantum yield of PSII was measured in the majority of cells with an altered chloroplast distribution, and positive Sytox green® death staining confirmed that most of these cells were dead. We conclude that although Coscinodiscus granii can sustain high irradiance it does not perform chloroplast high-light avoidance movements for photo-protection.